KONSEP AL-ITTIHAD MENURUT TASAWUF ABU YAZID AL-BUSTAMI - Rahma Yanti; Nunu Burhanuddin (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2023)
Among the teachings of Sufism is Al-Ittihad which was brought by Abu Yazid Al Bustami. This concept teaches about the unity between God and servants who have achieved holiness so that a Sufi who is already at the level of ittihad feels that he is one with God, one level shows that the one who loves and the beloved has become one, so that one of them can call the other. other. Al-Ittihad is achieved through fana and baqa. Fana is the destruction of the sense of awareness of the existence of the gross human body, what remains spiritually is human, for this reason, before entering the mortal stage, Sufis must pay attention to 4 things, namely Al-Sukr is a state between love and living creatures. Ash-Syatahat is a strange expression expressed by Sufis. Zawal Alhujab is a condition of a Sufi who no longer wants anything except Allah. Ghalbat Al-Syhud is the condition of a Sufi both in terms of feelings of awareness and witnessing reaching the peak of mortals then he forgets himself and there is nothing but Allah SWT